Aphid orientation and performance in glasshouses under different UV‐A/UV‐B radiation regimes. Issue 3 (28th May 2017) - Dáder, Beatriz; Moreno, Aránzazu; Gwynn‐Jones, Dylan; Winters, Ana; Fereres, Alberto
Abstract: Visual cues leading to host selection and landing are of major importance for aphids and evidence suggests that flight activity is very dependent on ultraviolet (UV)‐A radiation in the environment. At the same time research on insect plant hosts suggest that the UV‐B component can deter some pests via changes in secondary metabolite chemistry. Here, we examine the potential of UV (UV‐A/UV‐B) radiation to control insect pests in the glasshouse environment. We first examined artificial exposure to UV‐B and the potential to trigger morphological and biochemical modifications in pepper ( Capsicum annuum L., Solanaceae) with implications for the fitness of green peach aphid, Myzus persicae Sulzer (Hemiptera: Aphididae). UV‐B caused accumulation of leaf secondary metabolites and soluble carbohydrates, and stimulated photosynthetic pigments. However, UV‐B did not impact on foliar protein content and aphid performance was unaffected. Next, we studied how altering the UV‐A/UV‐B ratio environment affected aphid orientation and spatial distribution over time, either directly or by exposing plants to supplemental UV before insect introduction. Aphids directly settled and dispersed on their host pepper plants more readily in the presence of supplemental UV‐A and UV‐B. In the control treatment with ambient glasshouse UV‐A and UV‐B, insects remained more aggregated. Furthermore, insects were less attracted to peppers pre‐exposed to supplemental UV‐A and UV‐B radiation. Our results suggest that suppression of UV‐A and UV‐B inside the protected environment reduces aphid colonization and dispersal. Furthermore, application of moderate exposure of young pepper plants to supplemental UV‐B radiation could aid in protection from the colonization by phytophagous insects.